The relationship between caregivers' subjective social status and asthma symptoms and management for urban children. (1st February 2019) - Diep, Judy; Fagnano, Maria; Tremblay, Paul; Halterman, Jill S.
ABSTRACT: Objective: Subjective social status (SSS) is a person's perception of his/her social standing among others. We explored the relationship between caregivers' SSS and asthma symptoms, visits, and medication use among children with persistent asthma. Methods: We analyzed baseline data of children (3–10 years) from the SB-TEAM trial in Rochester, NY. Using a modified MacArthur Scale of SSS, caregivers rated themselves "a lot worse off" to "a lot better off" compared to 4 groups (e.g., neighbors). "Low SSS" was defined by a response of "a lot worse off" or "somewhat worse off" for any of the referent groups. Caregivers reported their child's asthma symptoms, healthcare visits for asthma, and medication use. Bivariate and multivariate statistics were used. Results: We found that, of the 230 children enrolled (participation rate:78%, 62% Black, 72% Medicaid), 29% of caregivers had low SSS. Caregivers with low SSS had more depressive symptoms (46% vs. 28%) and lower social support (69.1 vs. 77.7). In multivariable analyses, children of caregivers with low SSS had fewer symptom-free days/2 weeks (5.8 vs. 7.9, p = .01). While they were more likely to have a routine asthma visit in the past year (35% vs. 23%, adjusted p = .03), there was no difference in their use of preventive medication. Conclusions: Many caregivers of children with persistent asthma report low SSS. While children of these caregivers had fewer symptom-free days, they were not more likely to use preventive medications. Efforts are needed to support these caregivers to ensure optimal preventive care and reduce morbidity.